Autonomy and Ethnicity negotiating competing claims in multi-ethnic states - edited by Yash Ghai. (Cambridge Cambridge University Press, 2000)
Responses to ethnic conflicts in recent decades have ranged from oppression and ethnic cleansing to accommodations of ethnic claims through affirmative policies, special forms of representation, power sharing, and the integration of minorities. One of the most sought after, and resisted, devices for conflict management is autonomy. This book uses select countries including China, Canada, South Africa, former Yugoslavia and Australia to explore the dialectics of ethnicity and territory as mediated by a variety of forms of autonomy.
Keywords: Autonomy